INVESTIGATION OF POWER DEFINITIONS AND POWER FACTOR UNDER NON-SINUSOIDAL CONDITIONS - Kocatepe, Celal; Koroglu, Selim; Arikan, Oktay (YILDIZ TECHNICAL UNIV, 2005)
As the number of non-linear elements that are connected to the power systems increase, undesired effects due to these non-linear components also increase. The power factor, power definitions, power and energy measurement for non-sinusoidal voltage and current are getting importance. In this study, power terms change with respect to power factor for various networks with harmonics have been analysed. Furthermore, the changes in power due to connection as only resistive, inductive or capacitive elements to non-sinusoidal power sources have been represented. These changes have been represented by using equation (13) and Matlab program for the analysis.
Keywords: Harmonic; Apparent power; Distortion power; Power factor; Engineering